DETERMINATION OF GLUE JOINT SHEAR STRENGTH OF THERMALLY MODIFIED PINE (PINUS SILVESTRIS) AND BIRCH (BETULA PENDULA) IN COMPARISON WITH THE UNMODIFIED WOOD (Innovation in Woodworking Industry and Engineering design, 2026)
The aim of this study was to determine the glue joint shear strength of thermally modified pine (Pinus silvestris) and birch (Betula pendula) in comparison with the unmodified wood and to look at the possibilities of its simultaneous gluing on the same equipment in the same conditions. For the experiments used two types of glue: polyvinylacetate glue (PVAc) Kleiberit 303.0 and polyurethane glue Kleiberit PUR – 501.0. Afterwards glue joint ultimate strength in shear parallel to the grain was measured.